Impact of end stage renal disease on in-hospital outcomes of patients with systolic and diastolic heart failure (insights from the Nationwide Inpatient Sample 2010 to 2014). (1st September 2018) - Lemor, Alejandro; Hernandez, Gabriel A.; Lee, Shawn; Patel, Nish; Blumer, Vanessa; Badiye, Amit; Alfonso, Carlos; Fonarow, Gregg C.; Lindenfeld, JoAnn; Chaparro, Sandra
Abstract: Background: Heart Failure (HF) and end stage renal disease (ESRD) are associated with increased morbidity, mortality, and are responsible for an immense economic burden. We sought to evaluate the impact of ESRD in heart failure by using a national cohort. Methods: This is a retrospective cohort study using the National Inpatient Sample (NIS) of patients hospitalized with HF from 2010 to 2014. The primary outcome was in-hospital mortality. Multivariate regression was used for the statistical analysis. Results: We identified a total 1, 587, 172 patients with systolic HF and 1, 316, 220 with diastolic HF. Patients with systolic HF and ESRD had higher in-hospital mortality (4.6% vs 2.7% OR: 1.86, p < 0.001). The in-hospital mortality in diastolic HF and ESRD was 2.7% vs 2.5% in those without ESRD (OR:1.11, p = 0.03). Patients with systolic HF and ESRD had significantly higher rates of ICU admissions (OR: 1.56, p < 0.001), mean length of stay (+1.5 days, p < 0.001), median hospital costs (p < 0.001), and acute respiratory failure (OR: 1.58, p < 0.001). Similarly, patients with diastolic HF and ESRD also had significantly higher rates of ICU admissions (OR: 1.59, p < 0.001), acute respiratory failure (OR: 1.54, p < 0.001), mean length of stay (+1.1 days, p < 0.001), and median hospital costs (p < 0.001). Conclusion: ESRD is associated with significantly increased in-hospital mortality in HF but the increase is nearly two-fold (86%) for systolic HF and very modest (11%) in diastolic HF. However, hospital costs, ICU admissions, acute respiratory failure, and length of stay are similarly higher for patients with both systolic and diastolic HF and ESRD. Highlights: The prevalence of ESRD in patients admitted with HF is high and increasing. ESRD is associated with significantly increased in-hospital mortality in HF, with greater impact in systolic HF patients. The mean length of stay was longer, and hospitalization costs were greater in patients with systolic and diastolic heart failure if they had ESRD. There was a statistically significant trend towards a mortality decrease in all patients with HF without ESRD but not for those with ESRD.